Pharmacodynamic Evaluation of the Neutralization of Endotoxin by PMX622 in Mice - Lake, Philip (American Society for Microbiology, 2004)
Polymyxin B (PMB) binds to and neutralizes endotoxin, but its systemic clinical utility is limited by neuro- and nephrotoxicity. PMX622 is a covalent conjugate of PMB and Dextran-70 designed to retain the ability of PMB to neutralize endotoxin and to retain the favorable colloidal, pharmacokinetic, and metabolic properties of Dextran-70. PMX622 has demonstrated efficacy in a number of animal models and effectively neutralized endotoxin in phase I clinical trials. Here, we systematically evaluated the pharmacodynamic properties of PMX622 in a murine model of endotoxin-induced lethality in galactosamine-sensitized mice. PMX622 completely and dose dependently inhibited lethality in this model. A stoichiometric relationship was found between the endotoxin challenge dose and the dose of PMX622 needed for protection. PMX622 neutralized endotoxin from four different genera of gram-negative bacteria but not Neisseria meningitidis. PMX622 was significantly less toxic than PMB in the mouse, suggesting that PMX622 has a better margin of safety than PMB. The timing of PMX622 administration relative to endotoxin was crucial. PMX622 was active for several hours prior to the endotoxin challenge; however, PMX622 did not protect mice if administered ≥15 min after endotoxin challenge. This suggests that PMX622 would best be clinically used prophylactically rather than therapeutically. These studies will be crucial in designing and interpreting human clinical trials assessing PMX622 efficacy.